V4-Vertex Magic Labeling for Hypercubes - S. Kavitha, V. L. Stella Arputha Mary (Drugs and Cell Therapies in Hematology, 2021)
This article deals with the investigation of -vertex magic labeling on Hypercube, Double edge connected path union of hypercubes, Double edge connected open star of hypercubes and Double edge connected open star of path union of hypercubes.